LOCFAS–Assessed Evolution of Cognitive and Behavioral Functioning in a Sample of Pediatric Patients With Severe Acquired Brain Injury in the Postacute Phase. (August 2015) - Villa, Federica; Colombo, Katia; Pastore, Valentina; Locatelli, Federica; Molteni, Erika; Galbiati, Sara; Galbiati, Susanna; Strazzer, Sandra
We studied 86 patients with severe acquired brain injuries of different etiology, aged 0 to 18 years, in a condition of vegetative state or minimally conscious state. During neurorehabilitation, we administered the Level of Cognitive Functioning Assessment Scale every 2 weeks in order to describe and compare the progressive improvement in their cognitive-behavioral functioning and responsiveness in different etiologies. Patients with traumatic brain injury showed more favorable clinical outcomes. The higher the level of functioning at the first evaluation, the better the outcome, and the higher the Glasgow Coma Scale score, the higher the Level of Cognitive Functioning Assessment Scale level reached at the end of hospitalization. Patients with an apparently stable clinical picture, too, showed a change in their ability to interact with the environment. This study underlines the importance of an individualized and early cognitive-behavioral intervention protocol that can reveal minimal and fluctuating responses.